Efficacy and safety of dulaglutide 3.0 and 4.5 mg in patients aged younger than 65 and 65 years or older: Post hoc analysis of the AWARD‐11 trial. Issue 10 (8th July 2021) - Frias, Juan P.; Bonora, Enzo; Nevárez Ruiz, Luis; Hsia, Stanley H.; Jung, Heike; Raha, Sohini; Cox, David A.; Bethel, M. Angelyn; Konig, Manige
Abstract: Aim: To evaluate the efficacy and safety of dulaglutide 3.0 and 4.5 mg versus 1.5 mg when used as an add‐on to metformin in subgroups defined by age (<65 and ≥65 years). Materials and Methods: Of 1842 patients included in this post hoc analysis, 438 were aged 65 years or older and 1404 were younger than 65 years. The intent‐to‐treat (ITT) population, while on treatment without rescue medication, was used for all efficacy analyses; the ITT population without rescue medication was used for hypoglycaemia analyses; all other safety analyses used the ITT population. Results: Patients aged 65 years or older and those younger than 65 years had a mean age of 69.5 and 53.2 years, respectively. In each age subgroup, the reduction from baseline in HbA1c and body weight (BW), and the proportion of patients achieving a composite endpoint of HbA1c of less than 7% (<53 mmol/mol) with no weight gain and no documented symptomatic or severe hypoglycaemia, were larger for dulaglutide 3.0 and 4.5 mg compared with dulaglutide 1.5 mg, but the treatment‐by‐age interactions were not significant. The safety profile for the additional dulaglutide doses was consistent with that of dulaglutide 1.5 mg and was similar between the age subgroups. Conclusion: Dulaglutide doses of 3.0 or 4.5 mg provided clinically relevant, dose‐related improvements in HbA1c and BW with no significant treatment‐by‐age interactions, and with a similar safety profile across age subgroups.